A Study on Project-Based Learning (PjBL) Model and English Conversational Gambits in Classroom Speaking Practices - Dian Ardiansah (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2023)
Abstract. This study aims to determine the effectiveness of a contemporary teaching model of Project-Based Learning (PjBL) using English Conversational Gambits as language material, which focuses on improving students' speaking skills. However, this study examine students' attitudes toward implementing learning models in terms of behavioral, cognitive, and emotional aspects. This present study was conducted at a university in Tasikmalaya. This present study used quantitative and qualitative designs following the purpose of the present study. As the results of quantitative data, it was found that the sig. (2- tailed) of t-test value is .001 which is smaller than .05 value. The results showed that the used of PjBL model improves students' proficiency in speaking by optimizing the process of EFL teaching and learning using material of English conversational gambits. In addition, according to the qualitative data analysis, this study shows that most of the students showed a positive attitude toward the implementation of the learning model. This study demonstrated by implementing PjBL model with English Conversational Gambits can be alternative strategy in EFL instructional techniques that can improve students' speaking skills.Keywords: classroom speaking practices; English Conversation Gambits; Project-Based Learning (PjBL); students’ speaking proficiencyAbstrak. Penelitian ini bertujuan untuk mengetahui efektivitas model Pembelajaran Berbasis Proyek (PjBL) dengan metode Conversation Gambits atau pembukaan percakapan dalam meningkatkan kemampuan berbicara siswa dalam bahasa Inggris. Selain itu, penelitian ini juga mengkaji sikap siswa terhadap model pembelajaran yang diterapkan ditinjau dari aspek perilaku, kognitif, dan emosional. Penelitian ini telah dilaksanakan di salah satu universitas di Tasikmalaya. Pendekatan kuantitatif dan kualitatif digunakan dalam penelitian ini. Hasil analisis data dari pendekatan kuantitatif, ditemukan bahwa sig. (2-tailed) dan nilai pada uji-t adalah 0,001 lebih kecil dari 0,05. Temuan lainnya juga menunjukkan bahwa model PjBL dapat meningkatkan kemampuan berbicara bahasa Inggris siswa dengan mengoptimalkan penggunaan metode Conversation Gambit selama pembelajaran berlangsung. Dari analisis data kualitatif, ditemukan bahwa sebagian besar siswa menunjukkan sikap positif terhadap penerapan model pembelajaran PjBL dan Conversation Gambit. Penelitian ini menyarankan agar penerapan model PjBL dapat dikolaborasikan dengan Conversation Gambit sebagai salah satu strategi pengajaran dalam kelas EFL untuk meningkatkan kemampuan berbicara siswa.Kata kunci: kelas praktik berbicara; pembukaan percakapan; Pembelajaran Berbasis Proyek (PjBL); kemampuan berbicara siswa